Feasibility study of minimal prepared hydroflush screening colonoscopy. Issue 1 (February 2016) - Moshkowitz, Menachem; Fokra, Ahmad; Itzhak, Yoseph; Arber, Nadir; Santo, Erwin
Background: Although screening colonoscopy is effective for early detection of colorectal cancer (CRC), screening rates remain low. Multiple factors are thought to be responsible for the low rates of screening colonoscopy, but bowel preparation appears to be a key deterrent. Tolerability issues with bowel preparations may lead to poor patient compliance, inadequate colon cleansing, and reduced detection of colonic polyps. Aim: The aim of this article is to evaluate the feasibility, safety, and outcomes of minimally prepared intra-procedural hydroflush technique as an alternative to traditional bowel preparation in screening colonoscopy. Design: We conducted a prospective feasibility study of intraprocedural hydroflush technique aided by water-jet pumps and a mechanical suction novel device following minimal bowel preparation for CRC screening. Patients and methods: Nine procedures were performed in nine healthy individuals scheduled for routine screening colonoscopy. Preparation included mild diet restriction, laxative tablets two to three days prior to the procedure and two Fleet enemas one to two hours before the colonoscopy. The cleanliness of the colon was assessed by using the Boston bowel preparation scale. Insertion and withdrawal times were recorded. Results: Complete colonoscopy to the cecum was performed in all patients (100%). Mean time to the cecum was 5.78 ± 2.68 minutes, and mean withdrawal time was 15.33 ± 3.94 minutes. Endoscopic visualization of the entire mucosa was achieved in all cases with no colonoscopy repeated because of inadequate preparation. Four polyps have been detected and removed in three patients. Mild mucosal erosions were seen in some areas where the suction was used extensively, similar to those that can be seen during conventional colonoscopy. Mild stiffness of the shaft of the scope was noted. Limitations: This was an uncontrolled feasibility study of selected patients. Conclusions: Minimally prepared colonoscopy with the intra-procedural hydroflush technique for colorectal screening is feasible. The water exchange technology compensates for the mild stiffness of the scope. This technique might increase patients' compliance for CRC screening.